Teknik Pemanfaatan Limbah Pucuk Daun Tebu (Saccharum officinarum L.) untuk Pembuatan Pupuk Organik Cair - Marlina Marlina; Putri Wulandari (Seminar Nasional Lahan Suboptimal, 2018)
Marlina et al, 2019. The Usage Technic of Leaf tip of Sugarcane (Saccharum officinarum L.) as waste on Liquid Organic Fertilizer Production. pp. 430-435. Sugarcane waste by the usage in Liquid Organic Fertilizing (LOF) processing compressed the increase of sugarcane planting waste. The research aim was to study the sugarcane waste as the material for LOF production with EM4 contain microorganisms.Three levels of EM4 solution treatment on sugarcane leaf tip, which was keep in water on an aerob were conducted in Ketiau village, at Ogan Komering Ilir District. Sample physic of the Liquid was analyzed at Physiology Laboratory of Agriculture Faculty, Universitas Sriwijaya. The result showed the weight of solid and liquid, the percentage of soluble of liquid, also pH and color of the liquid, that was 200 ml of EM4 solution on the leaf tip sugarcane waste keeping in water in 25 days an aerob incubation maximalizing the LOF production. The conclusion, that leaf tip waste of sugarcane by using EM4 solution in water, an aerob incubation produced liquid  which was as a LOF potential.